Crystallization kinetics of poly(ethylene oxide) confined in semicrystalline poly(vinylidene) fluoride - Tamaño-Machiavello, Maria N. (2018)
Polymer blends based on poly(vinylidene fluoride) (PVDF) and poly(ethylene oxide) (PEO) have been prepared to analyze the crystallization kinetics of poly(ethylene oxide) confined in semicrystalline PVDF with different ratios of both polymers. Both blend components were dissolved in a common solvent, dimethyl formamide. Blend films were obtained by casting from the solution at 70 degrees C. Thus, PVDF crystals are formed by crystallization from the solution while PEO (which is in the liquid state during the whole process) is confined between PVDF crystallites. The kinetics of crystallization of the confined PEO phase was studied by isothermal and nonisothermal experiments. Fitting of Avrami model to the experimental DSC traces allows a quantitative comparison of the influence of the PVDF/PEO ratio in the blend on the crystallization behavior. The effect of melting and further recrystallization of the PVDF matrix on PEO confinement is also studied.